BOON OR BANE: A SYSTEMATIC REVIEW OF VIRTUAL REALITY APPLICATION IN LANDSCAPE ARCHITECTURE DESIGN STAGE - Asilah binti Abdul Mutalib, Zalina binti Ismail (Tanjung Malim, 2024)
BOON OR BANE: A SYSTEMATIC REVIEW OF VIRTUAL REALITY APPLICATION IN LANDSCAPE ARCHITECTURE DESIGN STAGE by Asilah binti Abdul Mutalib, Zalina binti Ismail